Neutrophilic superoxide production can assess pharmacological and pharmacogenetic β‐adrenoreceptor effects. Issue 8 (30th May 2016) - Reinartz, M. T.; Wetzke, M.; Happle, C.; Kälble, S.; Scherer, R.; Kabesch, M.; Seifert, R.
Abstract: Asthma can be controlled well in most patients by inhaled β‐adrenoreceptor (β2 AR) agonists and steroids. Poor response to β2 AR agonists is difficult to predict, especially in young children and by lung function testing, which may be affected by multiple influences. As an alternative approach, we analyzed ex vivo neutrophilic superoxide inhibition in response to β2 AR stimulation. In 60 healthy volunteers, this assay was unaffected by sex, age, smoking, atopy or asthma status. Furthermore, we assessed effects of genetic variants in β2 AR by sequencing the ADRB2 gene in our cohort and relating genotypes to β2 AR‐mediated neutrophilic superoxide inhibition. Gly16Arg genotypes correlated with minor decrease in overall adrenoresponse in this small study population. Taken together, ex vivo testing of the β2 AR response in human neutrophils represents a robust tool with good signal‐to‐noise ratio at physiological β2 AR agonist concentrations, and this assay may be useful to complement future pharmacogenetic studies in asthma.